LEGAL REGULATION OF CREDIT INSTITUTIONS ACTIVITIES IN THE REPUBLIC OF CROATIA AND THE EUROPEAN UNION - Pavković, Anita; Hlupić Radić, Dario (EU and comparative law issues and challenges series (ECLIC), 2018)
Credit institutions are financial institutions which main activities are taking deposits from those who have surplus of money and to grant credits to those who have deficit of money and who needs money for investment or spending. By providing its services, credit institutions perform an important social function which is transferring money from people or corporations who has surplus to the people who has deficit of money. In addition to these core banking services, credit institutions provide other services such as payment services, exchange services, investment services etc. By providing their services, credit institutions manage significant amounts of money collected from the public. In order to protect depositors and investors, credit institutions’ operations are heavily regulated by a number of legal rules and regulations. In this paper it will be presented an overview of the EU legal system which regulates the activities of credit institutions in European Union. Those rules and regulations also apply in the Republic of Croatia as one of the member of the European Union. It will be presented a single rulebook that is a legal base of EU Banking Union. In brief, the Regulation (EU) No. 575/2013 and Directive 36/2013/EU, which regulates access to the activity of credit institutions, prudential requirements for credit institutions and the prudential supervision of credit institutions. Also it will be presented the Directives 2014/49 / EU and 2014/59 / EU which regulates deposits insurance and recovery and resolution of credit institutions. Finally, an overview of the regulation development in Croatia starting since 1990 up to today will be given, including the laws transposing the above-mentioned EU directives.